2021
DOI: 10.1088/1742-6596/1796/1/012100
|View full text |Cite
|
Sign up to set email alerts
|

Development of STEM-integrated physics e-module to train critical thinking skills: The perspective of preservice teachers

Abstract: The 21st-industrial revolution has become a hot topic to be discussed, including in the field of education. A country must be able to compete globally from the aspects of modern science and technology, one of which is through education. Education requires learning materials as a reference in the 21st-century. The purpose of this study was to develop learning media in the form of electronic modules for students on critical-thinking skills. The method used was Research and Development (R&D) with 26 students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
0
7
0
1
Order By: Relevance
“…Researchers provided various hands-on activities e.g. creating models, simulations or devices (Amiruddin et al, 2021;Asri et al, 2021;Chai et al, 2020;Djulia & Simatupang, 2021;Mayasari et al, 2019;Rosana et al, 2021;Sumirat, 2019;Yulianti et al, 2022), conducting experiments (Azhar et al, 2022;Elfa Sari et al, 2021;Jannah et al, 2021) or doing field observations (Ngabekti et al, 2019). Researchers in our corpus reported that hands-on activity encourages participants to participate actively in the learning process.…”
Section: Student-centered Learningmentioning
confidence: 96%
See 1 more Smart Citation
“…Researchers provided various hands-on activities e.g. creating models, simulations or devices (Amiruddin et al, 2021;Asri et al, 2021;Chai et al, 2020;Djulia & Simatupang, 2021;Mayasari et al, 2019;Rosana et al, 2021;Sumirat, 2019;Yulianti et al, 2022), conducting experiments (Azhar et al, 2022;Elfa Sari et al, 2021;Jannah et al, 2021) or doing field observations (Ngabekti et al, 2019). Researchers in our corpus reported that hands-on activity encourages participants to participate actively in the learning process.…”
Section: Student-centered Learningmentioning
confidence: 96%
“…Other participants create graphs, simulations, learning webbased media (symbol, diagram, and picture mode representation), explain products verbally, and then report in written form (Chai et al, 2020;Utomo et al, 2020;Yulianti et al, 2022). In STEM-based media development, participants create diagrams (Arifanti et al, 2021), conduct observations (Ngabekti et al, 2019) and create projects or experiments (Elfa Sari et al, 2021;Jannah et al, 2021). Five articles have participants feel experience-based metaphors allowing a choice of project or design to create (Chai et al, 2020;Djulia & Simatupang, 2021;Sumirat, 2019), then solve real-life community problems (Mayasari et al, 2019;Rosana et al, 2021).…”
Section: Multiple Representationsmentioning
confidence: 99%
“…Previous research to develop critical thinking abilities has used e-modules based on CTL (Desnita et al, 2022), scientific approaches (Haryanto et al, 2021), ethnoscience-based guided inquiry (Kurniawan & Syafriani, 2021), STEM (Handayani et al, 2021), and Problem-based Learning (Sujanem et al, 2020). Nevertheless, research using e-modules based on the POE learning model has yet to be conducted to increase critical thinking skills.…”
Section: Introductionmentioning
confidence: 99%
“…The government's efforts to make it happen have also become the fundamental basis for preparing the Ministry of Education and Culture's strategies in education. One of them is applying the STEM (Science, Technology, Engineering, and Mathematics) approach and 21st-century skills training (Handayani et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…One of the efforts of educators to adapt to these online learning conditions is to create supporting media or teaching materials (Sari, 2020). Educators can create learning media that can support conditions and practical and effective media such as electronic modules that support students to learn independently with complete and adequate sources of knowledge (Handayani et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%